Apresiasi Sastra sebagai Sarana Penguatan Bahasa dan Karakter pada Anak Usia Sekolah Dasar - Habibi Musa (FKIP UNSULTRA, 2025)
Literary appreciation plays a strategic role in developing language skills and shaping the character of elementary school children. Through reading, listening, and responding to literary works such as folk tales, fables, children's poems, and fairy tales, students not only improve their literacy skills, but also absorb the moral and social values ​​contained in the works. This study aims to analyze various literatures that discuss the relationship between literary appreciation, strengthening language skills, and character building in elementary school children. The method used is a literature study by reviewing various journals, books, and scientific articles in the last five years. The results of the study show that literary appreciation activities have proven effective in improving vocabulary, listening skills, writing narratives, and speaking expressively. In addition, story elements that are full of moral messages also encourage the development of positive characters such as empathy, honesty, responsibility, and tolerance. Thus, literary learning that is integrated thematically and contextually in the curriculum can be an effective means of developing language skills while strengthening the character education of elementary school students. This study recommends a pedagogical approach that is fun, participatory, and reflective in children's literature appreciation activities.